Investigation on thermo-physical properties and thermal-hydraulic performance of TiO2-SiO2 nanofluids - Muhammad Nabil Fikri, Mohamad (2018)
The need of thermal performance in the system has increased in recent years and motivated the researchers to find a new method to enhance the heat transfer performance. One of the methods is the combination of two or more nanoparticles into a base fluid to form the nanofluids and it is known as hybrid/ nanofluids which can give better performance of heat transfer. The main challenge for the existing cooling system performance is to minimize the flow resistance while enhancing the heat transfer coefficients. Beside that, conventional heat transfer fluids including water, ethylene glycol and oil have limitation to absorb the heat due to their poor thermal properties values especially the thermal conductivity. Therefore, it is vital to develop techniques to enhance the performance of the cooling system. The aims of the experimental study are to investigate the thermo-physical properties, heat transfer performance and friction factor of TiO2-SiO2 nanofluids in a circular tube under turbulent flow. The TiO2-SiO2 nanofluids are prepared by using the two-step method for 0.5 to 3.0% volume concentration with nanoparticles mixture ratio of 50:50 and dispersed in a base fluid of water/EG mixture with 60:40 volume ratio. The measurements of thermal conductivity and dynamic viscosity were performed at a temperature range of 30 to 80 °C by using KD2 Pro Thermal Properties Analyser and Brookfield LVDV III Ultra Rheometer, respectively. The experimental determination of forced convection heat transfer is conducted in the Reynolds numbers range from 3,000 to 24,000 at a bulk temperatures of 30, 50 and 70 °C. The experiments are undertaken for constant heat flux boundary condition. The thermal conductivity of TiO2-SiO2 nanofluids was improved by increasing the volume concentration and temperature with 22.8% maximum enhancement compared with base fluid and 7.5% improvement compared with single TiO2 nanofluids. The viscosity showed evidence of being influenced by nanoparticles concentration and nanofluids temperature. The heat transfer coefficient of TiO2-SiO2 nanofluids is enhanced with increasing of volume concentration and temperature. It was observed that the maximum enhancement of convective heat transfer is 81% higher than the base fluid for volume concentration and temperature of 3.0% and 70 °C, respectively. Furthermore, the friction factor of TiO2-SiO2 nanofluids is slightly increased with volume concentration. The regression correlation model was developed from the experimental result for the thermal conductivity, dynamic viscosity, Nusselt number and friction factor. Finally, it can be concluded that the thermal-hydraulic performance of TiO2-SiO2 nanofluids improved further as compared to single TiO2 or SiO2 nanofluids. Therefore, it is recommended to use TiO2-SiO2 nanofluids in water/EG mixture (60:40) for the heat transfer applications at temperature of 70 °C and 3.0% volume concentration.